Hypoglycemic Potential of the Young Leave Methanolic Extract of Magnifera indica in Alloxan Induced Diabetic Rat - M., Ugbenyen Anthony; A., Odetola Adebimpe (Pakistan Journal of Nutrition, 2009)
The study was designed to investigate the hypoglycemic potential of Magnifera indica young leave methanolic extract in alloxan induced diabetic rat. Albino rats each weighing 100-200g were given a peritoneal injection of 120mg of Alloxan per kg body weight. After 7 days the blood glucose level of the animals were checked to ascertain a diabetic state. Those that were diabetic were selected for the study. Oral administration of Magnifera indica leave extract (0.5g/kg body weight) or (1.0g/kg body weight) for 14 days resulted in a significant reduction in blood glucose level from 171.4±4.58 (mg/dl) to 103.7±1.45 (mg/dl) in diabetic rat given 1.0g/kg body weight dose and from 134.2±10.34 (mg/dl) to 97.7±7.01 (mg/dl) in diabetic rat given 0.5g/kg body weight dose, dose dependent being more effective at 1.0g/kg body weight dose than 0.5g/kg body weight dose.